DIFFERENTIAL DIAGNOSIS BETWEEN RADICULAR CYST AND GRANULOMA USING CONE-BEAM COMPUTED TOMOGRAPHY AND ULTRASOUND EXAMINATIONS: A SYSTEMATIC REVIEW (CIPEEX, 2025)
Pulp tissue necrosis followed by colonization and infection of the root canal are decisive events in the onset of apical periodontitis. Root cysts and granulomas are the most prevalent inflammatory periapical pathologies. This systematic review was developed to analyze the possibility of differential diagnosis between root cysts and granulomas using cone-beam computed tomography (CBCT) and ultrasonography. Searches were performed in six electronic databases and three additional platforms to search for gray literature. All searches were performed by May 15, 2021. After excluding duplicate articles, 1,111 articles were identified. In phase 1, 35 studies were selected for full reading. In phase 2, 30 articles met the eligibility criteria and were included in this review, comprising 23 observational clinical studies and seven case reports. There was considerable variability in the methodological designs of the studies: different devices, protocols, and variables were studied. The ability of CBCT to establish the differential diagnosis of radicular cysts ranged from 60% to 80% and granulomas from 44% to 63%, while ultrasound showed 77% to 100% accuracy. Agreement for cyst diagnosis and 50% to 77% for granuloma diagnosis. The risk of bias in the studies was classified as low to moderate. CBCT and ultrasound examinations allow differential diagnosis between inflammatory periapical pathologies.
Keywords: endodontics; differential diagnosis; apical periodontitis; systematic review